Effects of natural marine sediments on CH4 hydrate formation: A combined experimental and molecular dynamics study - Yun Li; Junming Zhou; Jin Han; Tao Lv; Junxi Feng; Shengxiong Yang (Applied Clay Science, 2026)

Carbon/nitrogen composite induction of extracellular polymeric substances from Desulfovibrio desulfuricans enables Cu2S quantum dot biosynthesis - Guangwen Zheng; Weifeng Song; Zuoyi Yang; Yantong Gao; Qian Yin; Ziheng Song; Chuanying Tu; Keqin Zhou; Junming Bian; Jingfeng Peng; Xiangdan Zhang; Xiaoyan Bai (Journal of Environmental Chemical Engineering, 2026)

An interpretable daily runoff prediction model driven by multi-source data: dual attention-based CNN-LSTM model - Lei Zhang; Xinwu Liu; Qinli Yang; Junming Shao (Computers & Geosciences, 2026)

Ca isotope fractionation during precipitation of authigenic carbonates: A case study from the Haima cold seep, northern South China Sea - Jingya Cao; Junming Zhou; Junxi Feng; Jun Tao; Jie Xuan; Shengxiong Yang (Chemical Geology, 2026)

Balancing N₂O and NH₃ emissions with maize yield: Investigating the role of alternate drip irrigation and 3,4-dimethylpyrazole phosphate (DMPP) - Junming Liu; Yuanyuan Fu; Le Yang; Zhuanyun Si; Sunusi Amin Abubakar; Huijie Li; Tao Zhou; Ruiqi Ren; Hongchen Li; Peng Li; Bingcheng Si; Yang Gao; et al. (Soil and Tillage Research, 2026)

Taurine supplementation enhances myofiber development and muscle texture in juvenile Pacific white shrimp (Litopenaeus vannamei) fed low fish meal diets - Menglin Shi; Hongjie Xie; Fang Yang; Junming Deng; Beiping Tan; Shiwei Xie (Animal Feed Science and Technology, 2026)

Re‑sulfurization protects Fe(III) (oxyhydr)oxides in anoxic marine sediments of the South China Sea - Junming Zhou; Junxi Feng; Jingya Cao; Wenxiao Fan; Haiyang Xian; Jing Liu; Peng Yuan; Shengxiong Yang (Marine Geology, 2026)

A flow-direction guided spatiotemporal graph neural network (FD-STGNN) framework for multi-source soil moisture data fusion over the Qinghai-Tibet Plateau - Xinghao Li; Qinli Yang; Junran Yang; Junming Shao (Journal of Hydrology, 2026)

FengYuan: An End-to-End Global Weather Forecasting Model Driven by Multi-Source Observational Data - Zhaoming Liang; Yang Li; Yaqiang Wang; Yiheng Shi; Junming Chen; Fenghua Ling; Enda Zhu; Hai Wang; Lei Bai; Huabing Ke; Zhongyan Hu; Xiaoxu Liu; et al. (Journal of Meteorological Research, 2026)

Dual regulation of EPS protein structure by C/S composite induction enables controlled biosynthesis of ZnS quantum dots - Chuanying Tu; Zuoyi Yang; Weifeng Song; Guangwen Zheng; Jingfeng Peng; Keqin Zhou; Junming Bian; Yantong Gao; Qian Yin; Xiangdan Zhang; Xiaoyan Bai (Journal of Water Process Engineering, 2026)

Occurrence and characteristics of organochlorine pesticides from soils due to permafrost thaw slumping on the Qinghai-Tibetan Plateau - Xiaoyue Zhang; Lili Yang; Shiwei Sun; Shichang Kang; Junming Guo; Chenyan Zhao; Qingyu Guo; Minghui Zheng; Guorui Liu (Journal of Environmental Sciences, 2026)

A novel TaqMan-based RT-qPCR assay for the detection of PEDV and discrimination of the G2c subtype - Yicong Fan; Xiang Li; Jiawen Mo; Liang Weng; Shiyu Liu; Xu Song; Rongli Guo; Wei Wang; Mi Hu; Shanshan Yang; Yongxiang Zhao; Baochao Fan; et al. (Archives of Virology, 2026)

Fine-mapping and candidate gene analysis of qFF3.1 conferring fruit firmness in a modern tomato variety - Yunhao Han; Xin Li; Can Zhu; Yonglian Wang; Junling Hu; Shumin He; Saifeng Guo; Xiaoxiao Lu; Chunyang Pan; Zejun Huang; Yanmei Guo; Xiaoxuan Wang; et al. (Theoretical and Applied Genetics, 2026)

Reactivation of ancient landslides in complex tectonic settings: Insights from the long-term monitoring of Jiangdingya landslides on the northeastern Tibetan Plateau - Yang Xiaohui; Zhu Wenjie; Liu Xiaojie; Guo Nan; Xu Shuai; Hao Junming (Bulletin of Engineering Geology and the Environment, 2026)

BmC-LZM-like2/4 mediates antiviral defense against BmNPV via dorsal pathway - Junming Xia; Yifan Yang; Shigang Fei; Yigui Huang; Jiasheng Lin; Luc Swevers; Min Feng; Jingchen Sun (Pesticide Biochemistry and Physiology, 2026)

Spatial coordination and driving mechanisms of recreational service flow in typical plateau lake landscapes in China - Chenxi Gao; Junming Yang; Jun Qi (Journal of Environmental Management, 2026)

Abrupt temperature shifts alter DOM composition and electron transfer capacity: Unraveling the impact of climate extremes on greenhouse gas emissions in Yangtze River floodplain sediments - Junming Wu; Qiong Zhang; Ning-Xin Wang; Giri R. Kattel; Cheng-Gong Yang; Sven Frei; Zhi-Guo Yu (Environmental Research, 2026)

Rapid phosphorus adsorption: Polyaluminium chloride (PAC) modified glass pumice (MPAC-G) with exceptional regenerability for low-concentration aquaculture effluents - Junming Li; Jie Yang; Xiangying Wei; Xin Xu; Guifang Yang; Jianhui Huang; Xiuchun Lin; Yuancai Lv; Xiaomei Zhong; Zeyuan Zhao (Environmental Research, 2026)

3D hybrid chiral metamaterial with diverse lateral deformation behaviors: Theoretical, experimental, and numerical study - Yu Zhang; Weizhu Yang; Peijie Sun; Junming Huang; Na Yang; Lei Li (Engineering Structures, 2026)

Seasonal and architectural drivers of microbial and potential pathogen communities in dormitories - Junming Ye; Hafiz Adeel Ahmad; Zhengyu Chen; Dehong Chen; Yiqi Tao; Jiang Wu; Lei Su; Bo Yang; Tang Liu (Building and Environment, 2026)

Natural and anthropogenic factors exacerbating mercury ecological risk in the Qilian Mountain Rivers: A threat to water resources - Xiwen Miao; Shiwei Sun; Zhengzheng Yang; Shichang Kang; Yulan Zhang; Qianggong Zhang; Tanuj Shukla; Junming Guo; Yujiao Zhao; Jie Huang (Science China Earth Sciences, 2026)

PPIL1 promotes hepatocellular carcinoma progression and associates with poor prognosis - Yunyu Wu; Shuqing Jiang; Junming Yu; Hechun Lin; Saihua Zhang; Yizi Jin; Yang Su; Wenjiao Jin; Chao Ge; Qin Geng; Taoyang Chen; Jinjun Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrating water and nitrogen optimization to enhance wheat yield and macronutrients absorption under high-low seedbed cultivation - Shuang Li; Huijie Li; Jiahong Yang; Zhuanyun Si; Tao Zhou; Ruiqi Ren; Hongchen Li; Peng Li; Yanfang Liu; Junming Liu; Bingcheng Si; Yang Gao; et al. (Irrigation Science, 2026)

Massage therapy modulates energy metabolism and alleviates skeletal muscle spasms in rats - Jiawei Sun; Changhe Yu; Yang Zhang; Fenglin Li; Yanhua Wang; Eryang Liu; Junming Guo; Xiyou Wang; Zhifeng Liu (Tissue and Cell, 2026)

Powering shrimp growth: How Atractylodes macrocephala polysaccharide fuels Litopenaeus vannamei development through intestinal microbiota modulation - Xiping Chen; Junming Deng; Xiaohui Dong; Qihui Yang; Hongyu Liu; Shuang Zhang; Shiwei Xie; Wei Zhang; Beiping Tan; Shuyan Chi (Aquaculture, 2026)

Optimal selection and fusion framework of multi-source soil moisture data based on climate zoning and cross attention - Enhui Wang; Xinghao Li; Junran Yang; Junming Shao; Guoqing Wang; Qinli Yang (Journal of Hydrology, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

N6-methyladenosine attenuates tumor-associated macrophages M2 polarization via suppressing the translation of Snail - Yifan Tian; Jianxin Peng; Jiawang Zhou; Weifeng Yang; Yanxi Peng; Jianing Li; Yalan Rui; Haisheng Zhang; Guoyou Xie; Haoran Wang; Jiamin Wang; Jiexin Li; et al. (Science China Life Sciences, 2026)

Spatial distribution, influencing factors, and environmental risk assessments of mercury in surface soils over Xinjiang, northwestern China - Zhengzheng Yang; Shiwei Sun; Xiwen Miao; Shichang Kang; Pengfei Chen; Dipesh Rupakheti; Zhaofu Hu; Junming Guo (Journal of Environmental Sciences, 2025)

An Interpretable framework of Soil moisture estimation based on Mixture-of-Experts (ISMoE): a case study on the Tibetan Plateau - Junran Yang; Qinli Yang; Feichi Hu; Junming Shao (Journal of Hydrology, 2025)

Electrochemical impedance spectroscopy for pear ripeness detection and integration with robotic manipulators - Xunan Sui; Jiawen Zou; Zhonglin Geng; Hongjing Yang; Junming Hou; Longlong Feng (Food Control, 2025)

Water-saving management sustains yield of both ordinary paddy rice and drought-resistance rice varieties with reduced irrigation water in ratoon rice production of Central China - Chen Yang; Huiping Wang; Yucheng Wang; Guodong Yang; Meng Zhang; Xiangning Wu; Bin Wang; Le Xu; Junming Tu; Jie Chen; Zheng Qi; Kehui Cui; et al. (Field Crops Research, 2025)

Unlocking a thioglycolic acid-mediated fractionation strategy for high-whiteness and uncondensed lignin - Qiaolong Zhai; Jie Li; Kangze Miao; Shaoqi Yang; Yanju Lu; Qian Guan; Junming Xu; Jianjun Hu; Shuheng Zhao (Chemical Engineering Journal, 2025)

Long-term weed control alters arbuscular mycorrhizal fungal community and increases wheat yield in a rice-wheat cropping system of East China - Qiang Li; Jian Liu; Junming Shen; Yaguang Xue; Yafeng Wei; Zichang Zhang; Ali El-Keblawy; Mohamed S. Sheteiwy; Amal M. Fakhry; Haishui Yang (Pedobiologia, 2025)

C/S composite induction on spatial structure of EPS from Desulfovibrio desulfuricans subsp. and their adsorption performance of Zn(II) - Chuanying Tu; Zuoyi Yang; Weifeng Song; Guangwen Zheng; Jingfeng Peng; Keqin Zhou; Junming Bian; Xiangdan Zhang; Xiaoyan Bai (Journal of Water Process Engineering, 2025)

Synergistic modification engineering for optimizing reaction kinetics of direct carbon solid oxide fuel cells with agricultural solid waste as fuel - Junwei Hou; Fengjin Yang; Junze He; Jiahong Hong; Yunjin Yang; Yuzhi Li; Jieqin Ma; Tianhao Zhong; Junming Chen; Yuancheng Luo; Yiyao Yu; Fangyong Yu; et al. (Fuel, 2025)

Isolation and pan-genome analysis of Acinetobacter junii SC22, a heavy metal(loid)s resistant and plant growth promoting bacterium, from the Zijin Gold and Copper mine - Yuanping Li; Xiaojun Yang; Junming Su; Hend Alwathnani; Jianghua Ye; Christopher Rensing (BioMetals, 2025)

BaTiO3 dressed in carbon multifunctional layer achieving high areal capacity zinc metal batteries - Rui Wang; Jing Xu; Shijun Luo; Yan Guo; Baohe Yuan; Lei Xu; Junming Li; Yongqi Zhang; Yusheng Wang; Wenpeng Yang; Jinbing Cheng; Yongsong Luo (Chemical Engineering Journal, 2025)

Simulation-guided plasma surface engineering for enhanced triboelectric Nanogenerator performance - Hong Yu; Haonan Ma; Zuying Huang; Mengya Lin; Junming Chen; Ruibin Wu; Ye Tao; Chengrun Li; Ruijia Yang; Xiaozhen Du (Chemical Engineering Journal, 2025)

From glacier forelands to human settlements: Patterns, environmental drivers, and risks of antibiotic resistance genes - Binglin Zhang; Ruiqi Yang; Yang Liu; Junming Guo; Junhua Yang; Xiang Qin; Shijin Wang; Junlin Liu; Xiaoying Yang; Wei Zhang; Guangxiu Liu; Tuo Chen (Journal of Hazardous Materials, 2025)

Dietary bile acids reduced ferroptosis, improved the flesh quality and intestinal health of Pacific white shrimp (Litopenaeus vannamei) fed the high plant protein-based diets - Kangyuan Qu; Junwei Zeng; Junming Deng; Xiaohui Dong; Hongyu Liu; Shuang Zhang; Shuyan Chi; Qihui Yang; Beiping Tan; Shiwei Xie (Aquaculture, 2025)

Hydrolysis of myofibrillar proteins by protease AprA secreted from Pseudomonas fragi: Preference for degrading Ala-linked peptide bonds - Silu Liu; Liangting Shao; Yang Dong; Junming Gong; Xinqi Yang; Fang Li; Xinglian Xu; Huhu Wang (Food Chemistry, 2025)

An adaptive rainfall-runoff model for daily runoff prediction under the changing environment: Stream-LSTM - Feichi Hu; Qinli Yang; Junran Yang; Junming Shao; Guoqing Wang (Environmental Modelling & Software, 2025)

Decoding different oxidative stress pathways in periodontitis: a comparative review of mechanisms of traditional tobacco smoke and electronic smoke aerosol - Ruxia Hou; Jitong Yang; Xixi Li; Xinmei Wang; Wenxin Du; Wen Kang; Jiajia Liu; Tingting Yang; Junming Li; Xiangyu Wang; Junyu Liu; Bin Zhao (Archives of Toxicology, 2025)

The unique Co2Mn1N8 structure enhances peroxymonosulfate activation and singlet oxygen generation through a localized electric field - Xiuding Shi; Zhengyi Lu; Rou Tan; Ruisong Lan; Jiefeng Xiao; Qian Zhang; Han Feng; Junming Hong; Hongyi Yang (Chemical Engineering Journal, 2025)

Microplastic characteristics in rivers and lakes across the Tibetan Plateau - Ling Yang; Shichang Kang; Yulan Zhang; Zhaoqing Wang; Xi Luo; Junming Guo; Tanguang Gao (Journal of Mountain Science, 2025)

Hydrolyzing collagen by extracellular protease Hap of Aeromonas salmonicida: Turning chicken by-products into bioactive resources - Liangting Shao; Junming Gong; Yang Dong; Silu Liu; Xinglian Xu; Huhu Wang (Food Chemistry, 2025)

Integrative analysis of genetic variability and functional traits in lung adenocarcinoma epithelial cells via single-cell RNA sequencing, GWAS, bayesian deconvolution, and machine learning - Chenggen Gao; Jintao Wu; Fangyan Zhong; Xianxin Yang; Hanwen Liu; Junming Lai; Jing Cai; Weimin Mao; Huijuan Xu (Genes & Genomics, 2025)
Background Lung adenocarcinoma remains a leading cause of cancer-related mortality worldwide, characterized by high genetic and cellular heterogeneity, especially within the tumor microenvironment. Objective This study integrates single-cell RNA sequencing (scRNA-seq) with genome-wide association studies (GWAS) using Bayesian deconvolution and machine learning techniques to unravel the genetic and functional complexity of lung adenocarcinoma epithelial cells. Methods We performed scRNA-seq and GWAS analysis to identify critical cell populations affected by genetic variations. Bayesian deconvolution and machine learning techniques were applied to investigate tumor progression, prognosis, and immune-epithelial cell interactions, particularly focusing on immune checkpoint markers such as PD-L1 and CTLA-4. Results Our analysis highlights the importance of genes like SLC2A1, which regulates glucose metabolism and correlates with tumor invasiveness and poor prognosis. Immune-epithelial interactions suggest a suppressive tumor microenvironment, potentially hindering immune responses. Additionally, machine learning models identify core prognostic genes such as F12, GOLM1, and S100P, which are significantly associated with patient survival. Conclusions This comprehensive approach provides novel insights into lung adenocarcinoma biology, emphasizing the role of genetic and immune factors in tumor progression. The findings support the development of personalized therapeutic strategies targeting both tumor cells and the immune microenvironment.

Wet deposition of atmospheric Hg in a typical inland city in North China: Sources, influencing factors, and health risk assessment - Xiaofei Li; Wen Yang; Fei Gao; Ang Li; Lekhendra Tripathee; Junming Guo; Lang Liu (Environmental Pollution, 2025)

Analysis of various parameters in soaking: a case study of Permian Fengcheng Formation in Mahu Sag, Junggar Basin, China - Liu Yang; Wang Junming; Zhang Wenquan; Li Zhaolei; Zha Zhengtang (Arabian Journal of Geosciences, 2025)

Microplastics in glaciers of Tibetan Plateau: Characteristics and potential sources - Zhaoqing Wang; Shichang Kang; Yulan Zhang; Xi Luo; Qiangqiang Kang; Pengfei Chen; Junming Guo; Zhaofu Hu; Zhengzheng Yang; Huijun Zheng; Tanguang Gao; Wei Yang (Science of The Total Environment, 2024)

Mineral formation and element migration in fractures and pores of hydrogenetic ferromanganese nodules - Junming Zhou; Huan Zhang; Yanhui Dong; Wenxiao Fan; Jiangbo Ren; Shengxiong Yang (Chemical Geology, 2024)

Influencing Factors and Model of Shallow Gas Enrichment in the Quaternary Sediments of the Qiongdongnan Basin, South China Sea - Jianxiang Pei; Entao Liu; Peng Song; Detian Yan; Wei Luo; Junming Zhan; Zhenzhen Wang; Gupan Li; I. Tonguç Uysal; Peifeng Yang (Journal of Marine Science and Engineering, 2024)
Investigating the primary influencing factors that regulate the enrichment of shallow gas not only deepens our understanding of the rules governing shallow gas enrichment in deep-ocean environments but also has the potential to enhance the success rate of locating shallow gas reservoirs. Recent drilling activities in the LS36 gas field located in the central Qiongdongnan Basin have revealed a substantial shallow gas reserve within the sediments of the Quaternary Ledong Formation, marking it as the first shallow gas reservoir discovered in the offshore region of China with confirmed natural gas geological reserves surpassing 100 billion cubic meters. However, the formation mechanism and influencing factors of shallow gas enrichment remain elusive due to the limited availability of 3D seismic and well data. This study employs seismic interpretation and digital simulation to decipher the dynamics of shallow gas accumulation and utilizes the carbon isotope composition of methane to ascertain the origin of the shallow gas. Our results show that the shallow gas is primarily concentrated within a large-scale submarine fan, covering a distribution region of up to 2800 km2, situated in the deep-sea plain. The δ13 C1 methane carbon isotope data ranges from −69.7‰ to −45.2‰ and all δ13 C2 values are above −28‰, suggesting that the shallow gas within the Ledong Formation is derived from a mix of biogenic gas produced in shallow strata and thermogenic gas generated in deeper source rocks. The results of gas sources, seismic profiles, and digital simulations suggest that thermogenic gas originating from the Lingshui and Beijiao sags was transported to the Quaternary submarine fan via a complex system that includes faults, gas chimneys, and channel sands. The mass-transported deposits (MTDs) in the upper reaches of the submarine fan have effectively acted as a seal, preventing the escape of shallow gas from the fan. Therefore, the factors contributing to the enrichment of shallow gas in the Qiongdongnan Basin include the presence of favorable submarine fan reservoirs, the availability of two distinct gas sources, the effective sealing of MTDs, and the presence of two efficient transport pathways. A conceptual model for the accumulation of shallow gas is developed, illuminating the complex formation–migration–accumulation process. This study underscores the importance of aligning multiple influencing factors in the process of shallow gas accumulation, and the suggested accumulation model may be pertinent to shallow gas exploration in other marginal sea basins.

Comparisons of stripe rust response, grain yield and quality between fungicide sprayed and non-sprayed treatments for newly developed wheat lines carrying different genes for adult-plant resistance to stripe rust - Hao Chen; Liangqi Zhang; Chuanguang Ding; Yuqi Luo; Guoyun Jia; Junming Feng; Yuqi Wang; Binfan Si; Jianian Zhou; Xin Li; Kebing Huang; Suizhuang Yang; et al. (Crop Protection, 2024)

Formation of authigenic titania during the alteration of volcanic glasses in modern deep-sea environments - Jing Liu; Junming Zhou; Xiaodong Jiang; Zhenquan Wei; Shengxiong Yang (Geochimica et Cosmochimica Acta, 2024)

The structure and bioactivities of Stemona alkaloids and alkaloids with [1,2-α] azepine nucleus (2009–2021) - Yang Xu; Junming Liang; Yushu Yan; Dejuan Sun; Hua Li; Lixia Chen (Phytochemistry Reviews, 2024)

Sodium alginate/sodium lignosulfonate hydrogel based on inert Ca2+ activation for water conservation and growth promotion - Xinrui Zhang; Lifei Yang; Weicong Wang; Yuzhou Xiang; Jingshuai Liu; Yulong An; Junming Shi; Houjuan Qi; Zhanhua Huang (Environmental Research, 2024)

An untargeted metabolomics analysis of the components of heartwood and sapwood in 4 fast-growing Chinese fir (Cunninghamia lanceolata (Lamb.) Hook) clones - Xiaoqin Yang; Liping Li; Xiaorui Yu; Yun Liu; Sida Xie; Guolei Zhu; Junming Xu; Ping Zhao (Trees, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Multimodel ensemble estimation of Landsat-like global terrestrial latent heat flux using a generalized deep CNN-LSTM integration algorithm - Xiaozheng Guo; Yunjun Yao; Qingxin Tang; Shunlin Liang; Changliang Shao; Joshua B. Fisher; Jiquan Chen; Kun Jia; Xiaotong Zhang; Ke Shang; Junming Yang; Ruiyang Yu; et al. (Agricultural and Forest Meteorology, 2024)

The effect of broad bean diet on structure, flavor and taste of fresh grass carp: A comprehensive study using E-nose, E-tongue, TPA, HS-SPME-GC-MS and LC-MS - Bing Fu; Mengping Zheng; Huici Yang; Junming Zhang; Yichao Li; Guangjun Wang; Jingjing Tian; Kai Zhang; Yun Xia; Zhifei Li; Wangbao Gong; Hongyan Li; et al. (Food Chemistry, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

A climate-adaptive transfer learning framework for improving soil moisture estimation in the Qinghai-Tibet Plateau - Junran Yang; Qinli Yang; Feichi Hu; Junming Shao; Guoqing Wang (Journal of Hydrology, 2024)

Evaluation of seven satellite-based and two reanalysis global terrestrial evapotranspiration products - Zijing Xie; Yunjun Yao; Qingxin Tang; Meng Liu; Joshua B. Fisher; Jiquan Chen; Xiaotong Zhang; Kun Jia; Yufu Li; Ke Shang; Bo Jiang; Junming Yang; et al. (Journal of Hydrology, 2024)

Characteristics, sources, and health risk assessment of atmospheric particulate mercury in Guanzhong Basin - Xiaofei Li; Rui Zhang; Lekhendra Tripathee; Feng Yu; Jingning Guo; Wen Yang; Junming Guo; Shichang Kang; Junji Cao (Environmental Pollution, 2024)

An attention-mechanism-based deep fusion model for improving quantitative precipitation estimation in a sparsely-gauged basin - Hongyuan Liu; Qinli Yang; Zhaoyu Liu; Junming Shao; Guoqing Wang (Journal of Hydrology, 2024)

Paleoenvironmental Evolution and Organic Matter Accumulation in a Hydrocarbon-Bearing Depression in the East China Sea - Junming Zhan; Entao Liu; Si Chen; Qiyang Zhang; Yuyue Chen; Jialin Zhong; Yongkun Zhou; Peifeng Yang; Yangshuo Jiao (Journal of Marine Science and Engineering, 2023)
Investigating the paleoenvironment and characteristics of source rocks in sedimentary basins is crucial for understanding organic matter accumulation and guiding hydrocarbon exploration. The Lishui Sag, a significant hydrocarbon-bearing depression in the East China Sea, has experienced extensive marine transgression and increasing salinity in the Paleocene, but the changes in accumulation factors of organic matter during this evolution process remain unclear. Through a comprehensive analysis of total organic carbon (TOC), major and trace elements, and biomarker data, this study investigates the characteristics of source rocks from two lithostratigraphic units, namely the Paleocene Yueguifeng and Lingfeng formations, to gain deep insight into the effects of paleoenvironment on organic matter accumulation and hydrocarbon distribution. Our results indicate that the Lishui Sag transitioned from a closed lake to an open-marine environment in the Paleocene, with a shift from warm-humid to arid climate conditions. The biomarker distribution suggests a change in the origin of organic matter, with a higher input of terrestrial organic matter in the Lingfeng Formation. During the early stage, the lacustrine source rocks in the lower Yueguifeng Formation were formed in a relatively humid and anoxic environment within brackish water, resulting in a substantial influx of terrestrial and lacustrine algae organic matter. In contrast, in the late stage, the marine source rocks in the overlying Lingfeng Formation were developed in an arid and oxidizing environment. The lacustrine source rocks in the Yueguifeng Formation were notably more favorable to developing good-quality source rocks. Compared with the other regions, the western and northeastern parts of the study area have greater hydrocarbon generation potential due to the wider distribution of high maturity and organic-rich source rocks, with higher terrestrial and algal organic matter input. Moreover, considering the practical circumstances in the exploration, the northeastern part of the Lishui Sag is recommended as the next exploration target zone.

Enhanced U-Net model for rock pile segmentation and particle size analysis - Zhen Yang; Hao Wu; Haojie Ding; Junming Liang; Li Guo (Minerals Engineering, 2023)

Soil moisture at 30 m from multiple satellite datasets fused by random forest - Jing Ning; Yunjun Yao; Qingxin Tang; Yufu Li; Joshua B. Fisher; Xiaotong Zhang; Kun Jia; Jia Xu; Ke Shang; Junming Yang; Ruiyang Yu; Lu Liu; et al. (Journal of Hydrology, 2023)

Microstratigraphic geochemical characteristics of ferromanganese crust from central pacific: Implication for the role of Fe and Mn in REY enrichment - Junming Zhou; Jing Liu; Shengxiong Yang; Yanhui Dong; Jinfeng Ma; Peng Yuan (Chemical Geology, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Coupling a light use efficiency model with a machine learning-based water constraint for predicting grassland gross primary production - Ruiyang Yu; Yunjun Yao; Qingxin Tang; Changliang Shao; Joshua B. Fisher; Jiquan Chen; Kun Jia; Xiaotong Zhang; Yufu Li; Ke Shang; Junming Yang; Lu Liu; et al. (Agricultural and Forest Meteorology, 2023)

A high-yield and high-efficiency cultivation pattern of winter wheat in North China Plain: High-low seedbed cultivation - Zhuanyun Si; Junming Liu; Lifeng Wu; Sen Li; Guangshuai Wang; Jiachuan Yu; Yang Gao; Aiwang Duan (Field Crops Research, 2023)

Carbon budgets and environmental controls in alpine ecosystems on the Qinghai-Tibet Plateau - Wensi Ma; Tonghua Wu; Xiaodong Wu; Sizhong Yang; Ren Li; Shiqiao Zhou; Xiangfei Li; Xiaofan Zhu; Junming Hao; Jie Ni; Dong Wang (CATENA, 2023)

Coupling physical constraints with machine learning for satellite-derived evapotranspiration of the Tibetan Plateau - Ke Shang; Yunjun Yao; Zhenhua Di; Kun Jia; Xiaotong Zhang; Joshua B. Fisher; Jiquan Chen; Xiaozheng Guo; Junming Yang; Ruiyang Yu; Zijing Xie; Lu Liu; et al. (Remote Sensing of Environment, 2023)

A new few-shot learning model for runoff prediction: Demonstration in two data scarce regions - Minghong Yang; Qinli Yang; Junming Shao; Guoqing Wang; Wei Zhang (Environmental Modelling & Software, 2023)

Variations in water sources used by winter wheat across distinct rainfall years in the North China Plain - Junming Liu; Zhuanyun Si; Shuang Li; Abdoul Kader Mounkaila Hamani; Yingying Zhang; Lifeng Wu; Yang Gao; Aiwang Duan (Journal of Hydrology, 2023)

Flotation de-inking for recycling paper: contrasting the effects of three mineral oil-free offset printing inks on its efficiency - Shujie Yang; Jianbin Shen; Tiefei He; Chao Chen; Junming Wang; Yanjun Tang (Environmental Science and Pollution Research, 2022)

Vasorin contributes to lung injury via FABP4-mediated inflammation - Xiaoping Guo; Junming Sun; Jinning Liang; Siran Zhu; Mingyuan Zhang; Lichao Yang; Xuejing Huang; Kangning Xue; Zhongxiang Mo; Sha Wen; Bing Hu; Jiajuan Liu; et al. (Molecular Biology Reports, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Effects of Dietary Lipid Sources on Alleviating the Negative Impacts Induced by the Fishmeal Replacement With Clostridium autoethanogenum Protein in the Diet of Pacific White Shrimp (Litopenaeus vannamei) - Chaozhong Zheng; Shunlian Gong; Junming Cao; Xiaohui Dong; Shuyan Chi; Qihui Yang; Hongyu Liu; Shuang Zhang; Shiwei Xie; Beiping Tan (Frontiers in Marine Science, 2022)
This study evaluated the effects of lipid sources on the replacement of fishmeal with Clostridium autoethanogenum protein (CAP) in the diet of Pacific white shrimp ( Litopenaeus vannamei ). By using CAP to replace 40% fishmeal in the basal diet (contains 25% fishmeal), four diets (PC as the control diet, LSO as the low soybean oil level, MSO as the middle soybean oil level, and HSO as the high soybean oil level) were formulated by adding different proportions of fish oil and soybean oil. Each diet was assigned to four replicates (40 shrimps per replicate, initial weight = 1.79 ± 0.02 g). A 7-day Vibrio parahaemolyticus challenge test was conducted at the end of the 50-day feeding experiment. Weight gain was significantly higher and the cumulative mortality after challenge was lower in HSO treatment. The total antioxidant capacity (T-AOC) in hepatopancreas was significantly raised with increasing dietary soybean oil based on CAP substitution. After challenge, Pen3 mRNA expression was significantly higher in hepatopancreas and NF-κB pathway-related mRNA ( dorsal , relish , and IKKβ ) expression was higher in the intestine in HSO treatment. The height of mucosal folds and the thickness of the muscle layer were positively correlated with the level of dietary soybean oil. Transmission electron microscopy (TEM) analysis showed that the microvilli were damaged and the endoplasmic reticulum was swollen in shrimp fed the LSO diet. Diversity of intestinal microbiota was increased in shrimp fed the LSO diet, with a significant increase in beneficial bacteria such as Halocynthiibacter and Ruegeria as well as less harmful bacteria such as Vibrio . These results suggested that the replacement of fishmeal with CAP and the high proportion of soybean oil in the diet could improve the growth performance, disease resistance, and intestinal structure of Pacific white shrimp, and high fish oil in a low-FM diet raised the percentage of beneficial bacteria in the intestine of shrimp.

Occurrence of structural aluminium (Al) in marine diatom biological silica: visible evidence from microscopic analysis - Qian Tian; Dong Liu; Peng Yuan; Mengyuan Li; Weifeng Yang; Jieyu Zhou; Huihuang Wei; Junming Zhou; Haozhe Guo (Ocean Science, 2022)
The global marine biogeochemical cycle of aluminium (Al) is believed to be driven by marine diatoms, due to the uptake of dissolved Al (DAl) by living diatoms from surface seawater. The occurrence of Al in diatom biogenic silica (BSi) can inhibit the dissolution of BSi, thus benefiting the effects of the ballast role of diatoms in the biological pump and forming a coupled Si–Al biogeochemical cycle. However, the occurrence characteristic of Al in marine diatoms is still unclear. In particular, whether or not Al is incorporated into the structure of BSi of living diatoms is unrevealed, resulting in difficulties in understanding the biogeochemical behaviours of Al. In this study, Thalassiosira weissflogii, a widely distributed marine diatom in marginal seas, was selected as the model to evaluate the occurrence of structural Al in BSi based on culturing experiments with the addition of DAl. The structural Al in BSi was detected by combining focused ion beam (FIB) scanning electron microscopy and energy-dispersive X-ray spectroscopy (EDS) mapping analysis. Visible, direct evidence of structural Al in living BSi was obtained, and the distribution and content of this Al were revealed by the EDS-mapping analysis. The effects of structural Al on BSi dissolution–inhibition are discussed based on the content of this Al. The fundamental results indicate the significant contribution of marine diatoms to the biogeochemical migration of marine Al.

Mercury sources and physicochemical characteristics in ice, snow, and meltwater of the Laohugou Glacier Basin, China - Rukumesh Paudyal; Shichang Kang; Junming Guo; Lekhendra Tripathee; Chhatra Mani Sharma; Jie Huang; Yang Li; Fangping Yan; Kun Wang; Jizu Chen; Xiang Qin; Mika Sillanpaa (Environmental Science and Pollution Research, 2021)

The Single-Molecule Long-Read Sequencing of Intestine After Soy Meal-Induced Enteritis in Juvenile Pearl Gentian Grouper, Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂ - Wei Zhang; Beiping Tan; Junming Deng; Xiaohui Dong; Qihui Yang; Shuyan Chi; Hongyu Liu; Shuang Zhang; Shiwei Xie; Haitao Zhang (Frontiers in Marine Science, 2021)
Intestinal inflammatory disease induced by excessive soy protein substitutions for fish meal (FM) protein is a common phenomenon. The pearl gentian grouper, Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂, a marine fish with important economical and nutritional values, exhibited a similar problem. As far as we know, there are no reports on the full-length transcriptome of the pearl gentian grouper. In the present study, seven isonitrogenous and isolipidic (10% lipid) diets were prepared and fed to fish for 10 weeks. The water volume in each barrel was about 1 m 3 , using natural light and temperature. The results showed that 40% dietary soy proteins significantly negatively affected the growth performance of the pearl gentian grouper. Compared to the FM control, the content of immunoglobulin M and the enzyme activities of glutathione reductase, glutathione peroxidase, and total superoxide dismutase in the intestine significantly increased; the content of malondialdehyde in the intestine significantly decreased; and the enzyme activities of alanine transaminase and aspartate transaminase in the liver significantly increased. A library composed of seven different treated distal intestine tissues, including the FM control group, 20% soybean meal substitute for FM (SBM20), SBM40, 20% soybean protein concentrate (SPC20), SPC40, 20% fermented soybean meal substitute for FM (FSBM20), and FSBM40, was constructed and sequenced using PacBio single-molecule real-time (SMRT) and the RNA-Seq technology. As a whole, this study obtained 420,006 full-length non-chimeric (FLNC) reads. After error correction, sequence clustering, and redundancy, 82,351 transcripts with high quality were obtained. In addition, a total of 77,815 transcripts were annotated in seven databases (non-redundant protein sequences, non-redundant nucleotide sequences, Protein family, Clusters of Orthologous Groups of proteins, Gene Ontology, Swiss-Prot, and KEGG Orthology). Also, 49,093 long non-coding RNAs (lncRNAs) and 141,702 simple sequence repeats were identified. Based on full-length transcriptome sequencing, the present study found that the Toll-like receptor/nuclear factor kappa-B signaling pathway plays an important role in the development of SBM- and FSBM-induced enteritis. SPC-induced enteritis is mainly accompanied by a general imbalance of the nutrition absorption-related signaling pathways, which only affects a small part of the immune-related signaling pathways. This study supplies new and valuable reference transcripts, which would better facilitate further research on the pearl gentian grouper.

Immune characteristics distinguish patients with severe disease associated with SARS-CoV-2 - Xiaolei Li; Yang Liu; Junming Li; Longhua Sun; Jibin Yang; Fei Xu; Jing Zhou; Lagen Wan; Xinping Xu; Aiping Le; Wei Zhang (Immunologic Research, 2020)

Efficient photoreduction of Cr(VI) on TiO2/functionalized activated carbon (TiO2/AC-AEMP): improved adsorption of Cr(VI) and induced transfer of electrons - Zhao Gao; Hanpei Yang; Xiaofei Fu; Qiu Jin; Qiangshun Wu; Li Kang; Junming Wu (Environmental Science and Pollution Research, 2020)

Araneose Ti3+ self-doping TiO2/SiO2 nanowires membrane for removal of aqueous MB under visible light irradiation - Zhao Gao; Hanpei Yang; Jingtao Mao; Li Kang; Ruichen Zhang; Siqi Chai; Junming Wu; Wei Li (Environmental Science and Pollution Research, 2020)

Non-Gaussian Lagrangian Stochastic Model for Wind Field Simulation in the Surface Layer - Chao Liu; Li Fu; Dan Yang; David R. Miller; Junming Wang (Advances in Atmospheric Sciences, 2020)
Wind field simulation in the surface layer is often used to manage natural resources in terms of air quality, gene flow (through pollen drift), and plant disease transmission (spore dispersion). Although Lagrangian stochastic (LS) models describe stochastic wind behaviors, such models assume that wind velocities follow Gaussian distributions. However, measured surface-layer wind velocities show a strong skewness and kurtosis. This paper presents an improved model, a non-Gaussian LS model, which incorporates controllable non-Gaussian random variables to simulate the targeted non-Gaussian velocity distribution with more accurate skewness and kurtosis. Wind velocity statistics generated by the non-Gaussian model are evaluated by using the field data from the Cooperative Atmospheric Surface Exchange Study, October 1999 experimental dataset and comparing the data with statistics from the original Gaussian model. Results show that the non-Gaussian model improves the wind trajectory simulation by stably producing precise skewness and kurtosis in simulated wind velocities without sacrificing other features of the traditional Gaussian LS model, such as the accuracy in the mean and variance of simulated velocities. This improvement also leads to better accuracy in friction velocity (i.e., a coupling of three-dimensional velocities). The model can also accommodate various non-Gaussian wind fields and a wide range of skewness–kurtosis combinations. Moreover, improved skewness and kurtosis in the simulated velocity will result in a significantly different dispersion for wind/particle simulations. Thus, the non-Gaussian model is worth applying to wind field simulation in the surface layer.

White Matter Abnormalities in Major Depression Biotypes Identified by Diffusion Tensor Imaging - Sugai Liang; Qiang Wang; Xiangzhen Kong; Wei Deng; Xiao Yang; Xiaojing Li; Zhong Zhang; Jian Zhang; Chengcheng Zhang; Xin-min Li; Xiaohong Ma; Junming Shao; et al. (Neuroscience Bulletin, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Cambrian integrative stratigraphy and timescale of China - Maoyan Zhu; Aihua Yang; Jingliang Yuan; Guoxiang Li; Junming Zhang; Fangchen Zhao; Soo-Yeun Ahn; Lanyun Miao (Science China Earth Sciences, 2019)

Validation results of maximum S4 index in F-layer derived from GNOS on FY3C satellite - Weihua Bai; Yueqiang Sun; Junming Xia; Guangyuan Tan; Cheng Cheng; Guanglin Yang; Qifei Du; Xianyi Wang; Danyang Zhao; Yusen Tian; Xiaoxin Zhang; Mi Liao; et al. (GPS Solutions, 2019)

Common and distinct changes of default mode and salience network in schizophrenia and major depression - Junming Shao; Chun Meng; Masoud Tahmasian; Felix Brandl; Qinli Yang; Guangchun Luo; Cheng Luo; Dezhong Yao; Lianli Gao; Valentin Riedl; Afra Wohlschläger; Christian Sorg (Brain Imaging and Behavior, 2018)

Characterization of the temporal and spatial expression of wheat (Triticum aestivum L.) plant height at the QTL level and their influence on yield-related traits - Na Zhang; Xiaoli Fan; Fa Cui; Chunhua Zhao; Wei Zhang; Xueqiang Zhao; Lijuan Yang; Ruiqing Pan; Mei Chen; Jie Han; Jun Ji; Dongcheng Liu; et al. (Theoretical and Applied Genetics, 2017)

QTL detection for wheat kernel size and quality and the responses of these traits to low nitrogen stress - Fa Cui; Xiaoli Fan; Mei Chen; Na Zhang; Chunhua Zhao; Wei Zhang; Jie Han; Jun Ji; Xueqiang Zhao; Lijuan Yang; Zongwu Zhao; Yiping Tong; et al. (Theoretical and Applied Genetics, 2016)

Silencing the Double-Stranded RNA Binding Protein DGCR8 Inhibits Ovarian Cancer Cell Proliferation, Migration, and Invasion - Yuqi Guo; Peng Tian; Chuanhe Yang; Zhibing Liang; Min Li; Michelle Sims; Lu Lu; Zhan Zhang; Hongwei Li; Lawrence M. Pfeffer; Junming Yue (Pharmaceutical Research, 2015)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

Fine mapping of the Ph-3 gene conferring resistance to late blight (Phytophthora infestans) in tomato - Chunzhi Zhang; Lei Liu; Zheng Zheng; Yuyan Sun; Longxi Zhou; Yuhong Yang; Feng Cheng; Zhonghua Zhang; Xiaowu Wang; Sanwen Huang; Bingyan Xie; Yongchen Du; et al. (Theoretical and Applied Genetics, 2013)

Identification and mapping of quantitative resistance to late blight (Phytophthora infestans) in Solanum habrochaites LA1777 - Junming Li; Lei Liu; Yuling Bai; Richard Finkers; Feng Wang; Yongchen Du; Yuhong Yang; Bingyan Xie; Richard G. F. Visser; Adriaan W. van Heusden (Euphytica, 2011)

Combination of chemokine and angiogenic factor genes and mesenchymal stem cells could enhance angiogenesis and improve cardiac function after acute myocardial infarction in rats - Junming Tang; Jianing Wang; Fei Zheng; Xia Kong; Linyun Guo; Jianye Yang; Lei Zhang; Yongzhang Huang (Molecular and Cellular Biochemistry, 2010)

Adenovirus-mediated stromal cell-derived factor-1 alpha gene transfer improves cardiac structure and function after experimental myocardial infarction through angiogenic and antifibrotic actions - Junming Tang; Jianing Wang; Hongxian Song; Yongzhang Huang; Jianye Yang; Xia Kong; Linyun Guo; Fei Zheng; Lei Zhang (Molecular Biology Reports, 2010)

Effects of receptor activator of NF-κB ligand gene silencing on the human osteoblast-like MG63 cells - Min Zhao; Xingfen Yang; Junming Huang; Yilin Zhou; Jianbin Tan; Liantang Wang (Biologia, 2009)